Diagnostic values of adenosine deaminase cytokines in fluid contributed to the detection of extrapulmonary tuberculosis - Bui-Thi Thu Huong; Nguyen Minh Hien; Nguyen Tien Dung; Le-Thi Minh Hien; Luu Cong Thanh; Luu Vu Dung; Tran Khanh Chi; Nguyen-Van Khiem; Hoang Hai Yen (Italian Journal of Medicine)
Tuberculosis (TB) is a serious global public health problem. Detecting the changes of adenosine deaminase (ADA), interleukin (IL)-1β, IL-2, tumor necrosis factor-α (TNF-α), interferon-γ (IFN-γ) released from macrophages and monocytes is greatly valuable in the diagnosis of TB. Hence, this study was designed to determine the optimal cut-off points of ADA, IL-1β, IL-2, TNF-α, and IFN-γ, allowing to differentiate pleural TB (PLTB), peritoneal TB (PTB), and meningeal TB (MTB). The study included 386 patients with pleural effusion, 47 patients with peritoneal effusion, and 134 patients with encephalitis and meningoencephalitis suspect of TB. ADA was determined by an enzyme kinetics method; cytokine concentration was measured by a test based on the competitive enzyme-linked immunosorbent assay principle. Sensitivity, specificity, and positive and negative predictive value were calculated and described. In the aspiration fluid, ADA activity was greatly different between PLTB, PTB, and MTB groups with values of 37.5 U/L, 30.5 U/L, and 8.1 U/L and sensitivity and specificity of 87.7% and 83.4%; 100% and 88.9%; 97.3% and 98.6%, respectively. Similar, IFN-γ concentrations were distinctively different between PLTB, PTB, and MTB patients (with values of 120 pg/mL, 200 pg/mL, and 30 pg/mL with sensitivity and specificity of 80.3% and 80.9%; 80.0% and 92.6%; 98.6% and 61.7%, respectively). The determination of ADA and IFN-γ levels in the aspiration fluid is potentially considered a highly sensitive and specific test for differentiating PLTB, PTB, and MTB.